Feasibility and acceptability of a single-session perioperative acceptance and commitment therapy workshop for preventing chronic postsurgical pain: a single-arm, non-randomized pilot trial - Yamin, Jolin B.; Wilson, Jenna M.; Pester, Bethany D.; Allen, Caroline; Yoon, JiHee; Cornelius, Marise C.; Dharmendran, Diya; Steinhilber, Kylie; Crago, Madelyn; Kazemipour, Savannah; Franqueiro, Angelina; Fentazi, Delia; et al. (Frontiers in Pain Research, 2025)
ObjectiveThis pilot trial evaluated the feasibility, acceptability, and preliminary effects of a single-session, group-based Acceptance and Commitment Therapy (ACT) intervention for patients undergoing spine surgery (SS) to prevent chronic postsurgical pain (CPSP).MethodsForty-five adults (Mage = 64 years) scheduled for SS enrolled and were asked to complete baseline questionnaires, and 28 attended a 5 h virtual ACT workshop, which focused on enhancing psychological flexibility and acceptance. Feasibility was assessed by tracking enrollment and attendance, while treatment credibility, expectancy, and helpfulness were evaluated using the Credibility and Expectancy Questionnaire (CEQ) and the Treatment Helpfulness Questionnaire (THQ). Health-related outcomes, including pain severity and interference (Brief Pain Inventory; BPI), anxiety, and depression (PROMIS-29), were measured at baseline, 1-month, 3-months, and 6-months post-surgery.ResultsOf the enrolled participants, 58% attended the workshop, all of whom completed the entire workshop. CEQ and THQ scores indicated high credibility and helpfulness immediately after the intervention and at 1-month post-surgery. Exploratory analyses examining health outcome changes following ACT during the post-surgery period revealed that pain severity and interference, depression and anxiety all decreased over time.DiscussionThese findings suggest that a single-session ACT intervention is feasible and acceptable for patients undergoing SS and may enhance both pain-related functioning and improve psychological outcomes following surgery. Future research should explore the efficacy of this approach in larger, randomized controlled trials to further establish its impact on CPSP prevention.